PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN E-COMMERCE TIKTOK SHOP DI KECAMATAN SEBERANG ULU II PLAJU PALEMBANG - Andela, Resthie; Resthie Andela , Resthie Andela; Puspasari, Mardiana; Geby Gisela Syaputri, Ayu (Program Studi Manajemen Keuangan Syariah, 2026)
This study aims to determine the effect of Service Quality and Price simultaneously and partially on Customer Satisfaction of the TikTok Shop e-commerce platform in Seberang Ulu II, Plaju, Palembang District. The object of this research is consumers of TikTok Shop, with a total sample of 100 respondents. The sampling technique used was purposive sampling. This research employed an associative research design. The data used in this study consisted of primary and secondary data. Data collection techniques included questionnaires and documentation. The data analysis technique applied was Multiple Linear Regression. The results showed that the variables of Service Quality and Price have positive regression coefficients, indicating that both variables have a positive effect on Customer Satisfaction. The F-test results revealed that Fcount > Ftable (163.692 > 2.36) with a significance level of 0.000 < 0.10, meaning that Service Quality and Price simultaneously have a significant effect on Customer Satisfaction of TikTok Shop e-commerce in Seberang Ulu II, Plaju, Palembang District. Furthermore, the t-test results indicated that Service Quality has a significant effect on Customer Satisfaction because tcount > ttable (5.225 > 1.660), and Price also has a significant effect on Customer Satisfaction because tcount > ttable (7.838 > 1.660). The coefficient of determination (R Square) was 0.771 (77.1%), which means that 77.1% of the variation in Customer Satisfaction can be explained by Service Quality and Price, while the remaining 22.9% is influenced by other variables not included in this study.